2004
DOI: 10.1111/j.1365-2249.2004.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination encoding glutamic acid decarboxylase can enhance insulitis and diabetes in correlation with a specific Th2/3 CD4 T cell response in non-obese diabetic mice

Abstract: SUMMARYDNA vaccination encoding b cell autoantigens has been shown very recently to prevent type I diabetes in non-obese diabetic (NOD) mice. However, DNA vaccination encoding microbial or reporter antigens is known to induce specific long-lasting CD4 Th1 and strong cytolytic CD8 T cell responses. As this immune phenotype is associated strongly with b cell destruction leading to diabetes, we have chosen to study the effects of plasmids encoding glutamic acid decarboxylase (GAD), a crucial b cell autoantigen, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We have undertaken the so far most extensive study in HLA-A*0201 patients, using a large panel of epitopes and an IFN-␥ ELISPOT assay, and shown that IDDM patients can be distinguished from controls with a sensitivity and specificity both Ͼ80%, even when a limited panel of only five epitopes is used (14,16). Thus, satisfactory methods may now be available to detect HLA-A2-restricted islet-specific CD8 ϩ T cells in human peripheral blood, and such methods might soon be extended to additional HLA class I alleles, using efficient strategies such as epitope mapping by DNA immunization of HLA class I humanized mice (14,22).…”
Section: Nsulin-dependent Diabetes Mellitus (Iddm)mentioning
confidence: 99%
“…We have undertaken the so far most extensive study in HLA-A*0201 patients, using a large panel of epitopes and an IFN-␥ ELISPOT assay, and shown that IDDM patients can be distinguished from controls with a sensitivity and specificity both Ͼ80%, even when a limited panel of only five epitopes is used (14,16). Thus, satisfactory methods may now be available to detect HLA-A2-restricted islet-specific CD8 ϩ T cells in human peripheral blood, and such methods might soon be extended to additional HLA class I alleles, using efficient strategies such as epitope mapping by DNA immunization of HLA class I humanized mice (14,22).…”
Section: Nsulin-dependent Diabetes Mellitus (Iddm)mentioning
confidence: 99%
“…pc-GAD were previously described (40). The catalytic domain of IA-2 was amplified by PCR (TaqDNA polymerase; Promega) from ICA512.bdc pCRII (provided by Dr. C. Levy-Marchal, Hospital Robert Debré, Paris, France) using a sense oligonucleotide containing an EcoRI site (5Ј-GGAATTCTAACAT GGACATCTCCACGGG-3Ј; MWG) and an antisense primer containing an XbaI site (5Ј-CGGGCCCTCTAGAGCCTGGGGCAGGGCCTT-3Ј).…”
Section: Plasmid Construction and Mouse Immunizationsmentioning
confidence: 99%
“…Recombinant proteins produced by transiently transfected mammalian cells (293T cells) were detected by immunoblotting. HHDII mice were randomly allocated and DNA vaccinated twice at 6-wk intervals as previously described (40). …”
Section: Plasmid Construction and Mouse Immunizationsmentioning
confidence: 99%
“…To date, a series of different DNA vaccine strategies have been used in the NOD mice to induce Agspecific tolerance, but with variable outcomes. Routes of administration (i.e., intradermal, i.m., or oral), choice of Ag, as well as coadministration of Ag-coding and IL-coding plasmids determine protection versus acceleration of T1D in this model (8)(9)(10)(11)(12)(13). In most cases, these experiments have been carried out without a detailed analysis of the Ag-specific T cell response due to the lack of suitable reagents.…”
mentioning
confidence: 99%